2020
DOI: 10.5812/archcid.104621
|View full text |Cite
|
Sign up to set email alerts
|

Association of Underlying Diseases and Clinical Characteristics with Mortality in Patients with 2019 Novel Coronavirus in Iran

Abstract: Objectives: The first case of 2019 novel coronavirus disease (COVID-19) was reported in Iran in February 2020. Here, we report the epidemiological and clinical characteristics of patients with COVID-19 and factors associated with mortality in these patients. Methods: A retrospective cohort study was conducted from February 22, 2020, to March 24, 2020, in Golestan Hospital in Kermanshah, Iran. Demographic data including underlying diseases and clinical data including the presenting symptoms, chest computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…In another similar study in Iran, dyspnea was the most common symptom in patients [16], Our results showed that 32.60 % of patients had a history of an underlying disease which this rate was 18.48 % [16] and 34.9% [10] in other studies. In contrast, /diabetic disease was the most contributor to disease in the present study, but study [16] declared cardiovascular disease was the most. Six out of 92 patients (6.52%) required mechanical ventilation, in contrast, whit other study results which this rate was 13(10.83%) [8].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In another similar study in Iran, dyspnea was the most common symptom in patients [16], Our results showed that 32.60 % of patients had a history of an underlying disease which this rate was 18.48 % [16] and 34.9% [10] in other studies. In contrast, /diabetic disease was the most contributor to disease in the present study, but study [16] declared cardiovascular disease was the most. Six out of 92 patients (6.52%) required mechanical ventilation, in contrast, whit other study results which this rate was 13(10.83%) [8].…”
Section: Discussionsupporting
confidence: 57%
“…However, in other studies fever was the most common symptom [10,14,15]. In another similar study in Iran, dyspnea was the most common symptom in patients [16], Our results showed that 32.60 % of patients had a history of an underlying disease which this rate was 18.48 % [16] and 34.9% [10] in other studies. In contrast, /diabetic disease was the most contributor to disease in the present study, but study [16] declared cardiovascular disease was the most.…”
Section: Discussionsupporting
confidence: 40%
“…After deleting duplicates, we identified 2463 studies from four databases and then screened articles by title and full text according to the study's objectives. Finally, 69 studies were included in the meta-analysis (Figure 1), of which 62 studies had assessed risk factors for death from COVID 2889 ); 13 studies determined risk factors for severity (( 41,50,5355,65,…”
Section: Resultsmentioning
confidence: 99%